The magic of a common language : Jakobson, Mathesius, Trubetzkoy, and the Prague Linguistic Circle - Toman, Jindrich (Current studies in linguistics series, 1995)
Driven by a common desire to form a new basis for understanding the sources and functioning of language, a heterogeneous group of Czech, Russian, Ukrainian, and German scholars who found themselves living in Prague in the mid 1920's created the profoundly influential Prague Linguistic Circle. This book examines the historical factors that produced the Circle, the basic tenets that it promulgated, and, most important, the social and cultural environment in which it flourished. The book can also be read as an interlocking series of intellectual biographies of the Prague Circle's major figures. The new linguistics, whose core was to be phonology, emphasized synchronic analysis, anti-psychologism, anti-causalism, the investigation of language contact, and the understanding of language as a social institution. Significantly, the Circle's theories were strongly connected to and reflected by Prague's literary and artistic avant-garde.